Oxidative azacyclization of 1-monosubstituted thioureas in reaction with [bis(acyloxy)iodo]arenes to form 1,2,4-thiadiazole derivatives; Tetrahedron; Vol. 59, № 38 - Mamaeva E. A. Elena Andreevna (2003, 2003)
Title screen